Association of Anemia with Parathyroid Hormone Levels and Other Factors in Patients with End-Stage Renal Disease Undergoing Hemodialysis: A Cross-Sectional, Real-World Data Study in Pakistan - Humera Bukhari; Aneeqa Ahmad; Amna Noorin; Aimal Khan; Mehwish Mushtaq; Aamir Naeem; Muhammad Rashid Iqbal; Faiza Naureen; Yasar Shah; Ahad Qayyum; Syed Munib; Amer Azhar; et al. (International Journal of Clinical Practice)
End-stage renal disease (ESRD) patients are mostly managed with maintenance hemodialysis (MHD). ESRD patients on MHD also present with many complications, such as anemia, hyperparathyroidism, and hepatitis prevalence. This study depicts the real-world scenario of anemia among MHD and end-stage renal disease patients in the Pakistani population. A retrospective, multicentric, and real-world data analytical study was conducted at 4 dialysis centers in Pakistan. The study had a sample size of n = 342 patients on maintenance hemodialysis. The data were gathered from the medical records of patients. Data analysis was performed using STATA Version 16. Statistical significance was gauged at a 0.05 level of significance. According to our results, the mean age of the patients was 45 (±15) years. Most of the patients were male (n = 234, 68.4%), whereas 58.1% of the patients were maintained on twice-weekly hemodialysis. The most commonly reported comorbidities were hypertension and diabetes mellitus. The frequency of dialysis (P < 0.01) and comorbidities (P = 0.009) had a significant association with anemia in MHD patients. The majority of the patients had hyperparathyroidism (52%) with anemia. Upon performing binary logistic regression, multivariate analysis displayed a similar odds value for having anemia in patients with every additional month in the duration of hemodialysis (OR 1.01, P = 0.001), the odds of anemic patients having a positive antihepatitis-C antibody (OR 2.22, P = 0.013), and the odds of having anemia in patients in the age category below 45 years (OR 1.93, P = 0.013). In conclusion, the study results depict that every additional month in the duration of hemodialysis, age (<45 years), and positive anti-HCV antibody status, these variables were more likely to have anemia in our study MHD patients. While in our final multivariate model, no statistically significant association was observed between hyperparathyroidism and anemia.